2002
DOI: 10.1056/nejmoa020423
|View full text |Cite
|
Sign up to set email alerts
|

A Program to Prevent Functional Decline in Physically Frail, Elderly Persons Who Live at Home

Abstract: A home-based program targeting underlying impairments in physical abilities can reduce the progression of functional decline among physically frail, elderly persons who live at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
566
2
27

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 745 publications
(607 citation statements)
references
References 26 publications
12
566
2
27
Order By: Relevance
“…However, the remarkable increase in life span has also led to an important increase in frailty and dependency (Gill et al 2002). It is clear now that we must aim at increasing health span.…”
Section: Introductionmentioning
confidence: 99%
“…However, the remarkable increase in life span has also led to an important increase in frailty and dependency (Gill et al 2002). It is clear now that we must aim at increasing health span.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of all participants was 79 years, and 69% of the participants were women (supplementary materials/appendix 1). The methodological quality of included trials varied; seven trials (Hall et al 1992;Leveille et al 1998;Mann et al 1999;Dalby et al 2000;Rockwood et al 2000;Chin et al 2001;Phelan et al 2004;Holland et al 2005) were of low quality according to the criteria (van Tulder et al 2003), and seven trials were of high quality (Dalby et al 2000;Stuck et al 2000;van Haastregt et al 2000;Hebert et al 2001;Gill et al 2002Gill et al , 2004Gitlin et al 2006a;b;Markle-Reid et al 2006) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a total of 19 articles (Hall et al 1992;Leveille et al 1998;Mann et al 1999;Dalby et al 2000;Rockwood et al 2000;Stuck et al 2000;van Haastregt et al 2000;Chin et al 2001;Hebert et al 2001;Chin et al 2002;Gill et al 2002Gill et al , 2004Phelan et al 2004;Holland et al 2005;Gitlin et al 2006a;b;Markle-Reid et al 2006;Bouman et al 2008a, b), all RCTs concerning communitydwelling persons 65 years or older identified as frail, vulnerable, at risk of functional decline, having disabilities or chronic conditions and receiving multi-component HPDP interventions were included for detailed review (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations